Projections in donor organs available for liver transplantation in the United States: 2014‐2025. Issue 6 (June 2015) - Parikh, Neehar D.; Hutton, David; Marrero, Wesley; Sanghani, Kunal; Xu, Yongcai; Lavieri, Mariel
Abstract : With the aging US population, demographic shifts, and obesity epidemic, there is potential for further exacerbation of the current liver donor shortage. We aimed to project the availability of liver grafts in the United States. We performed a secondary analysis of the Organ Procurement and Transplantation Network database of all adult donors from 2000 to 2012 and calculated the total number of donors available and transplanted donor livers stratified by age, race, and body mass index (BMI) group per year. We used National Health and Nutrition Examination Survey and Centers for Disease Control and Prevention historical data to stratify the general population by age, sex, race, and BMI. We then used US population age and race projections provided by the US Census Bureau and the Weldon Cooper Center for Public Service and made national and regional projections of available donors and donor liver utilization from 2014 to 2025. We performed sensitivity analyses and varied the rate of the rise in obesity, proportion of Hispanics, population growth, liver utilization rate, and donation after cardiac death (DCD) utilization. The projected adult population growth in the United States from 2014 to 2025 will be 7.1%. However, we project that there will be a 6.1% increase in the number of used liver grafts. There is marked regional heterogeneity in liver donor growth. Projections were significantly affected by changes in BMI, DCD utilization, and liver utilization rates but not by changes in the Hispanic proportion of the US population or changes in the overall population growth. Overall population growth will outpace the growth of available donor organs and thus potentially exacerbate the existing liver graft shortage. The projected growth in organs is highly heterogeneous across different United Network for Organ Sharing regions. Focused strategies to increase the liver donor pool are warranted. Liver Transpl 21:855‐863, 2015 . © 2015 AASLD.